2019
DOI: 10.1186/s13071-019-3375-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma-associated antigen 59 of Haemonchus contortus modulates the functions of PBMCs and the differentiation and maturation of monocyte-derived dendritic cells of goats in vitro

Abstract: BackgroundHepatocellular carcinoma-associated antigen 59 (HCA59), which is one of the most important excretory/secretory products of Haemonchus contortus (HcESPs), is known to have antigenic functions. However, its immunomodulatory effects on host cells are poorly understood.MethodsHere, we cloned the HCA59 gene and expressed the recombinant protein of HCA59 (rHCA59). Binding activities of rHCA59 to goat peripheral blood mononuclear cells (PBMCs) and dendritic cells (DCs) were checked by immunofluorescence ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
(71 reference statements)
3
17
0
Order By: Relevance
“…Moreover, increased migration rate of immune effector cells was observed in vitro. The proliferation results of this study are in line with the results of the previous study [58]. In contrast, cell proliferation was suppressed after PBMCs were treated with rHcARF1 [59].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, increased migration rate of immune effector cells was observed in vitro. The proliferation results of this study are in line with the results of the previous study [58]. In contrast, cell proliferation was suppressed after PBMCs were treated with rHcARF1 [59].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was identified that goat PBMC proliferation increased at a significant level which ultimately showed constant apoptosis of PBMC in response to rHc-GDC treatment. The proliferation results of the present study are in line with the results of the previous study [5]. In contrast, cell proliferation was suppressed after PBMCs were treated with rHcARF1 [41].…”
Section: Discussionsupporting
confidence: 93%
“…Hosts become infected after the ingestion of third-stage infective larvae (L3). Bloodfeeding adult H. contortus can lead to severe hemorrhagic gastritis, anemia, hypoproteinemia, edema, and even death in acute infections [5][6][7]. Control of this parasitic nematode is based on the application of anthelmintics, but excessive usage of these drugs has led to the development of anthelmintic resistance [8][9][10][11].…”
mentioning
confidence: 99%
“…Subsequently, the Trizol method was used to extract RNA from cell sediments using primescript RT reagent kit (Takara, CA, USA) as per manufacturer's instruction. The cDNA-based quantifications of cytokine transcriptions were evaluated as described previously [31] using specific primer sequences (S1 Table), and β-actin was used as a reference gene (β-actin). The data were analyzed based on raw cycle threshold (Ct), obtained from the ABI Prism 7500 software (Applied Biosystems, USA) by comparative Ct (2−ΔΔ Ct) Method (26).…”
Section: Evaluation Of Tgf-β/smad Signalingmentioning
confidence: 99%
“…Subsequently, the Trizol method was used to extract RNA from cell sediments using primescript RT reagent kit (Takara, CA, USA) as per manufacture's instruction. The cDNA-based quantifications of cytokine transcriptions were evaluated as described previously [31]. The primer sequences were designed (F, GATGCGGCTGATTGTTT, R, and CTCGTGCTCACTGTGGAGT) and used for IL-9 cytokine determination.…”
Section: Determination Of Il-9 Cytokinementioning
confidence: 99%